TaFROG Encodes a Pooideae Orphan Protein That Interacts with SnRK1 and Enhances Resistance to the Mycotoxigenic Fungus Fusarium graminearum. Issue 4 (27th October 2015) - Perochon, Alexandre; Jianguang, Jia; Kahla, Amal; Arunachalam, Chanemougasoundharam; Scofield, Steven R.; Bowden, Sarah; Wallington, Emma; Doohan, Fiona M.
Abstract : A Pooideae orphan protein that enhances plant resistance against a toxigenic fungus physically interacts with a key signaling protein. Abstract: All genomes encode taxonomically restricted orphan genes, and the vast majority are of unknown function. There is growing evidence that such genes play an important role in the environmental adaptation of taxa. We report the functional characterization of an orphan gene ( Triticum aestivum Fusarium Resistance Orphan Gene [ TaFROG ]) as a component of resistance to the globally important wheat ( T. aestivum ) disease, Fusarium head blight. TaFROG is taxonomically restricted to the grass subfamily Pooideae . Gene expression studies showed that it is a component of the early wheat response to the mycotoxin deoxynivalenol (DON ), which is a virulence factor produced by the causal fungal agent of Fusarium head blight, Fusarium graminearum . The temporal induction of TaFROG by F. graminearum in wheat spikelets correlated with the activation of the defense Triticum aestivum Pathogenesis-Related-1 ( TaPR1 ) gene. But unlike TaPR1, TaFROG induction by F. graminearum was toxin dependent, as determined via comparative analysis of the effects of wild-type fungus and a DON minus mutant derivative. Using virus-induced gene silencing and overexpressing transgenic wheat lines, we present evidence that TaFROG contributes to host resistance to both DON and F. graminearum . TaFROG is an intrinsically disordered protein, and it localized to the nucleus. A wheat alpha subunit of the Sucrose Non-Fermenting1-Related Kinase1 was identified as a TaFROG-interacting protein based on a yeast two-hybrid study. In planta bimolecular fluorescence complementation assays confirmed the interaction. Thus, we conclude that TaFROG encodes a new Sucrose Non-Fermenting1-Related Kinase1-interacting protein and enhances biotic stress resistance.